Kemampuan Literasi Matematis Siswa SMP Ditinjau dari Self-Efficacy - Mutiara Pertiwi; Suhendra Suhendra; Dadang Juandi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2022)
Mathematical literacy is an individual’s ability to formulate, employ, and interpret mathematics in various contexts. One of the factors that influence this ability is self-efficacy. This study aims to obtain an overview of the mathematical literacy ability of junior high school students in terms of self-efficacy. The research method used is qualitative research with a phenomenological approach. The instruments used were researchers as the research implementer, a self-efficacy scale, a mathematical literacy ability test, and interview guidelines. The subjects of this study were three students who had filled out the self-efficacy scale, consisting of one student with a high level of self-efficacy, one student with a moderate level of self-efficacy, and one student with a low level of self-efficacy. The results show that student with a high level of self-efficacy can meet three indicators of mathematical literacy ability and use the knowledge gained from their experience in solving problems, student with a moderate level of self-efficacy can meet two indicators of mathematical literacy ability and tend to try to solve the given problem, meanwhile student with a low level of self-efficacy only meet one indicator of mathematical literacy ability and less aware of the role of mathematics in everyday life.